A novel facilely prepared rhodamine-based Hg2+ fluorescent probe with three thiourea receptors. (April 2016) - Hong, Miaomiao; Lu, Shengzhou; Lv, Feng; Xu, Dongmei
Abstract: A novel rhodamine-based turn-on fluorescent probe with three thiourea receptors was designed, synthesized and fully characterized. In acetonitrile/4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid buffer (9/1, v/v, pH = 7.21), the probe showed high selectivity and sensitivity to Hg 2+ with a 20-fold fluorescence enhancement at 583 nm. The increase in fluorescence intensity was linearly proportional to the concentration of Hg 2+ in the range of 25–200 μM with a detection limit of 3.04 × 10 −7 M. The probe could work in a nearly neutral pH span of 6.41–8.33 and exhibited excellent interference immunity. Real sample assay showed the probe had good practicability. The results from Job's plot, reversibility experiment, mass and infrared spectra analysis suggested a 1:3 probe/Hg 2+ complex with an association constant of 9.88 × 10 11 M −3 and a new interaction way between the probe and Hg 2+ . Highlights: A facilely prepared new rhodamine–thiourea conjugate is reported. The dye is a fluorescent probe for Hg 2+ with good overall performance. The probe formed a rare 1:3 complex with Hg 2+ . A new interaction way between Hg 2+ and the probe is discussed.